Renal Cortical Fibrinolytic Activity in the Rabbit Following One or Two Doses of Endotoxin - Bergstein, Jerry M.; Michael, Alfred F., Jr (Thrombosis and Haemostasis, 1973)
A fibrin slide technique has been utilized to study the effect of endotoxin on renal cortical fibrinolytic activity in the rabbit. Lytic activity was absent in kidney tissue obtained from animals given one injection of endotoxin and after development of the generalized Shwartzman reaction. Cortical lytic activity was not inhibited following in vitro incubation of tissue sections in phosphate-buffered saline solutions containing high concentrations of endotoxin.It is suggested that the initial injection of endotoxin may prepare for the generalized Shwartzman reaction by depletion of cortical fibrinolytic activity. The failure of endotoxin to inhibit tissue plasminogen activator in vitro suggests that endotoxin-induced loss of lytic activity is mediated through humoral factors.